P26 P38 MAPK Inhibition Enhances Corticosteroid Effects In Human Epithelial Cells Via Increased Gr Nuclear Localisation. (10th November 2014) - Lea, S; Gaffey, K; Plumb, J; Gaskell, R; Singh, D
Abstract : Background: Phospho-p38 MAPK expression is increased in airway epithelial cells in patients with severe asthma and in COPD patients compared to controls. Increased p38 MAPK activation may lead to reduced corticosteroid responsiveness. We have used a human cell bronchial epithelial cell line to investigate the effects of a p38 MAPK inhibitor in combination with a corticosteroid on inflammatory cytokine stimulation. Methods: The human epithelial cell line 16HBE14o - was used to determine the effects of dexamethasone (0.1–1000 nM) alone, the p38 MAPK inhibitor BIRB-796 (1–1000 nM) alone and both drugs combined at all concentrations on LPS (1 µg/ml), Poly I:C (100 µg/ml) or TNFα (10 ng/ml) -induced IL-6, IL-8 and RANTES. 16HBE14o - cells were treated with BIRB-796 (1–1000 nM) alone and in combination with dexamethasone (0.1 nM) for 30 min and glucocorticoid receptor (GR) nuclear translocation determined by immunofluorescence. The effects of TNFα stimulation on the phosphorylation of p38 and GR (serine 226) in 16HBE14o - cells were determined by Western blot analysis. Results: Maximum inhibition of dexamethasone and BIRB-796 in combination was significantly greater than either drug alone for LPS and TNFα induced IL-6 and IL-8 and for Poly I:C induced RANTES (p < 0.05 all comparisons). BIRB-796 (1000 nM) alone had no effect on GR translocation. BIRB-796 (1000 nM) used in combination with dexamethasone (0.1 nM) significantly increased nuclear GR (76.6% nuclear staining) compared to dexamethasone (0.1 nM) alone (4% nuclear staining). TNFα stimulation increased both p38 and GR serine 226 phosphorylation by 15 min. Pre-incubation with BIRB-796 abolished p38 phosphorylation and reduced GR serine 226 phosphorylation. Conclusion: P38 MAPK inhibition enhances the effect of corticosteroids on inflammatory cytokines in human epithelial cells. This enhancement is due to inhibition of p38 dependent phosphorylation of GR serine 226 which leads to increased nuclear localisation of GR.